Antibacterial Activity of Ulin Fruit Extract (Eusideroxylon zwageri) Against Bacteria Causes in Human Infections: Antibacterial Activity of Ulin Fruit Extract (Eusideroxylon zwageri) Against Bacteria Causes in Human Infections - Wina Annisa; Dede Mahdiyah; Darini Kurniawati (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
Infectious diseases one of the main health problem, especially in developing countries and have been recorded to cause more than 3 million people to die every year. Therapy used is antibacterial, but currently there are many occurrences of resistance to antibacterials, for example by the bacteria Salmonella typhi, Escherichia coli, and Staphylococcus aureus so it’s necessary to find antibacterial alternatives to treat infectious diseases. Non-pharmacological therapy used is the Ulin plant (Eusideroxylon zwageri), such as it’s fruit which contains secondary metabolites that function as antibacterial. This research aimed to identify the antibacterial activity of the Ulin fruit extract against Salmonella typhi, Escherichia coli, and Staphylococcus aureus bacteria. The type of research used is True Experimental with a Posttest-Only Control Group design. Screening antibacterial activity of Ulin fruit extract against Salmonella typhi, Escherichia coli, and Staphylococcus aureus bacteria using the well diffusion method and determining antibacterial activity test using the Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC) methods, then the data were analyzed using One Way Anova Test. The results show Ulin fruit extract has antibacterial activity with highest inhibition zone at concentration of 10 mg/ml against Salmonella typhi 19,07 mm, Escherichia coli 12,57 mm, and Staphylococcus aureus 12,31 mm and each has strong antibacterial activity. MIC at concentration of 5mg/ml. The results of statistical analysis showed significance value of 1,000 (p>0.05), meaning that there was no significant difference. So, Ulin fruit extract (Eusideroxylon zwageri) has antibacterial activity with a Minimum Inhibitory Concentration (MIC) value of 5mg/ml.